2010 - year of celebration of nursing - Maria Vera Lúcia Moreira Leitão Cardoso (Rev Rene)
The year 2010 is recognized as the International Year of Nursing in celebration of the centenary of the death of Florence Nightingale (1820-1910), renowned figure who emphasized the history of Modern Nursing. Florence showed her differentiated thinking concerning the nurse’s performance in a more critical view, with highlighted contributions around the world.